Demographic and clinical profile of children with severe acute malnutrition: an experience from nutritional rehabilitation centre in South Kashmir - Najar, Bilal Ahmad; Bhat, Mohd Ashraf; Rather, Zul Eidain; Sheikh, Mushtaq Ahmad (International Journal of Contemporary Pediatrics, 2021)
Background: Malnutrition is significant contributor of childhood morbidity and mortality in developing countries. More than 1/3rd of world’s severely malnourished children live in India. The aim was to evaluate the clinical-epidemiological profile and co-morbidities of SAM (severe acute malnutrition) children and to recognize socio-demographic risk factors of SAM children. Methods: It was a prospective hospital based case study. The prospective hospital based study was conducted from September 2018 to February 2020 and included children less than 5 years admitted to an paediatrics ward and satisfying the WHO definition of SAM. Data were entered in Microsoft excel sheet and SPSS software version 16 for windows was used for analysis. Results: 112 patients were taken for study. Mean age of admitted children were 16±3 months. Male:female ratio was 1:1.22. SAM is more common in nuclear families (N=67, 59.83%), illiterate mothers (N=72, 62.48%), children with high birth order more than 3 (N=42, 37%) and low socioeconomically status Kuppaswamy IV (N=72, 64.28%).The most common associated infections were acute gastroenteritis (82.14) and respiratory tract infections (54.20%). Hypoglycaemia (14.28) was the most common metabolic complication. The most commonly used supplementary food used was over diluted cow milk (43.67%). Conclusions: The problem of SAM is multifactorial (rural background, low socioeconomic status, maternal illiteracy, incomplete immunization). The findings of this study confirm the association of severe acute malnutrition with appropriate infant and young child feeding practices. NRCS provide life-saving care for children.